Prognostic Significance of Canine Mammary Tumor Histologic Subtypes: An Observational Cohort Study of 229 Cases. (July 2017) - Rasotto, Roberta; Berlato, Davide; Goldschmidt, Michael H.; Zappulli, Valentina
Histopathology is considered the gold standard diagnostic method for canine mammary tumors. In 2011, a new histologic classification for canine mammary tumors was proposed. The present study was a 2-year prospective study that validated the 2011 classification as an independent prognostic indicator with multivariate analysis in a population of 229 female dogs, identifying subtype-specific median survival times (MST) and local recurrence/distant metastasis rates. Dogs with benign tumors and carcinoma arising in benign mixed tumors all had an excellent prognosis. Dogs with complex carcinoma and simple tubular carcinoma also experienced prolonged survival. Those with simple tubulopapillary carcinoma, intraductal papillary carcinoma, and carcinoma and malignant myoepithelioma had a more than 10-fold higher risk of tumor-related death. The prognosis was even worse for adenosquamous carcinoma (MST = 18 months), comedocarcinoma (MST = 14 months), and solid carcinoma (MST = 8 months). The most unfavorable outcome was for anaplastic carcinoma (MST = 3 months) and carcinosarcoma (MST = 3 months), which also had the highest metastatic rates (89% and 100%, respectively). Adenosquamous carcinoma exhibited the highest local recurrence rate (50%). In the same canine population, the tumor diameter was recognized as a strong predictor of local recurrence/distant metastasis and an independent prognosticator of survival in the multivariate analysis. Excision margins were predictive only of local recurrence, whereas lymphatic invasion and histologic grade were predictive of local recurrence/distant metastasis and survival, although only in univariate analyses. In conclusion, this study validated the 2011 classification scheme and provided information to be used in the clinical setting and as the basis for future prognostic studies.